2011
DOI: 10.1007/s00213-010-2149-4
|View full text |Cite
|
Sign up to set email alerts
|

Residual effects of esmirtazapine on actual driving performance: overall findings and an exploratory analysis into the role of CYP2D6 phenotype

Abstract: IntroductionEsmirtazapine is evaluated as a novel drug for treatment of insomnia.PurposeThe present study was designed to assess residual effects of single and repeated doses of esmirtazapine 1.5 and 4.5 mg on actual driving in 32 healthy volunteers in a double-blind, placebo-controlled study. Treatment with single doses of zopiclone 7.5 mg was included as active control.MethodsTreatments were administered in the evening. Driving performance was assessed in the morning, 11 h after drug intake, in a standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 35 publications
4
38
0
Order By: Relevance
“…For zopiclone 7.5 mg evening doses were found to produce residual driving impairment in the morning in several studies (Vermeeren et al 1998a(Vermeeren et al , 2002bLeufkens et al 2009b;Ramaekers et al, 2011). As expected, the residual effects after MOTN administration were even larger (Vermeeren et al 1998a).…”
Section: Hypnoticssupporting
confidence: 48%
See 3 more Smart Citations
“…For zopiclone 7.5 mg evening doses were found to produce residual driving impairment in the morning in several studies (Vermeeren et al 1998a(Vermeeren et al , 2002bLeufkens et al 2009b;Ramaekers et al, 2011). As expected, the residual effects after MOTN administration were even larger (Vermeeren et al 1998a).…”
Section: Hypnoticssupporting
confidence: 48%
“…For instance, esmirtazapine is metabolised through CYP2D6 and its clearance is twice as low in poor metabolisers as compared with extensive metabolisers. A recent study showed a more pronounced driving impairment in poor metabolisers after treatment with esmirtazapine (Ramaekers et al 2011). This suggests that subjects with genetic CYP deviations (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 2-week placebo-controlled study of 1.5, 3.0, and 4.5 mg of esmirtazapine in patients with chronic primary insomnia, changes in all measures of the residual effect were similar in the esmirtazapine and placebo groups [13]. In another study, which assessed the residual effects of esmirtazapine in healthy volunteers by evaluating actual driving performance, single doses of 4.5 mg were associated with residual daytime impairment, but this generally resolved after repeated administration [19]. Indeed, in an earlier randomized, double-blind, placebo-controlled, dose-finding study with esmirtazapine, there were reductions in daytime "energy" and "ability to work/function" with all doses (1.5, 3, and 4.5 mg) relative to placebo after the first but not the second night of treatment [20].…”
Section: Discussionmentioning
confidence: 86%